The Effect of Aromatherapy by Inhalation and Massage on Radiotherapy-induced Fatigue in Patients With Cancer - Mojgan Moradi; Alice Khachian; Farshad Amini Behbahani; Kiarash Saatchi; Hamid Haghani (Iran University of Medical Sciences, 2020)
Background: Fatigue is one of the most prevalent and debilitating complications of cancer and its treatments. Patients undergoing radiotherapy experience some degrees of fatigue. Complementary medicine methods have reduced the complications of treatments in many disorders. Accordingly, the present study was conducted to compare the effect of aromatherapy by inhalation and massage on radiotherapy-induced fatigue in patients with cancer. Methods: In this randomized clinical trial, 105 patients with cancer undergoing radiotherapy in the oncology ward of Firouzgar Hospital in Tehran, Iran were selected conveniently based on the inclusion criteria and were randomly assigned into three groups of inhalation aromatherapy, massage aromatherapy, and control groups. In the first group, viola and almond oil were inhaled, in the second group, the Swedish massage was performed using aromatic oil, and the control group received routine care. Fatigue was measured by the Multidimensional Fatigue Inventory (MFI) before, and at the end of the intervention. The data were analyzed by descriptive and inferential statistics (ANOVA, Paired T-tests, Fischer's exact, and Chi-square tests) using SPSS software V. 16. The significance level was considered as P≤0.05. Results: The findings showed that the three studied groups had no significant statistical difference in terms of demographic characteristics before the intervention. Fatigue score was significantly different in all three groups after both interventions (P<0/001), which indicated a decrease in fatigue in the two test groups. However, according to Scheffe post hoc test, massage aromatherapy was more effective in reducing fatigue resulting from radiotherapy. Conclusion: The results of this study showed that massage aromatherapy was more effective in reducing radiotherapy-induced fatigue in patients with cancer. It is recommended that future studies recruit another group that receives the only massage.